2020
DOI: 10.1007/s10902-020-00261-5
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Gratitude as a Resource for Sustainable Mental Health: Results of a 3-Armed Randomized Controlled Trial up to 6 Months Follow-up

Abstract: The aim of the current study was to evaluate the impact of a 6-week gratitude intervention for people with low to moderate well-being and moderate symptomatology of depression and anxiety up to 6 months follow-up. 217 Dutch adults were randomly assigned to one of three conditions: a 6-week gratitude intervention, a 6-week self-kindness intervention as an active control condition and a waitlist control condition. Participants completed online assessments on well-being, depression, anxiety and gratitude at basel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 64 publications
(93 reference statements)
2
31
0
Order By: Relevance
“…Reviews found limited and inconclusive evidence for the efficacy of mainly brief gratitude interventions ( Wood et al, 2010 ; Davis, 2016 ; Dickens, 2017 ). However, recent studies showed a substantial impact on mental health of gratitude interventions of longer duration (Heckendorff et al, 2018; Bohlmeijer et al, 2021 ).…”
Section: Gratitudementioning
confidence: 99%
“…Reviews found limited and inconclusive evidence for the efficacy of mainly brief gratitude interventions ( Wood et al, 2010 ; Davis, 2016 ; Dickens, 2017 ). However, recent studies showed a substantial impact on mental health of gratitude interventions of longer duration (Heckendorff et al, 2018; Bohlmeijer et al, 2021 ).…”
Section: Gratitudementioning
confidence: 99%
“…In the current study, we observed that those parents who wrote about perspective taking and gratitude showed a decrease in their negative affect pre-to post-writing, relative to parents who did not reflect on this topic. Reflecting on gratitude has been successfully used as a psychotherapeutic intervention to improve wellbeing and reduce stress [76][77][78] . A study during COVID-19 showed that daily reflections on gratitude increased employees' work satisfaction 79 , while another study involving college students showed that pre-COVID-19 levels of expressed gratitude were predictive of a reduced negative impact of the pandemic on student academic performance 80 .…”
Section: Discussionmentioning
confidence: 99%
“…Forgers, compared to Reflectors, also reported enhanced gratitude (McCullough et al, 2004) from experiencing the pandemic. Gratitude can act as a psychosocial resource for mental health in dealing with life changes (e.g., Bohlmeijer et al, 2020). Gratitude involves recognition of simple pleasures and abundance, even in the face of loss.…”
Section: Emerging Adults' Personality Profiles: Adapting To the Covid...mentioning
confidence: 99%